Geographical information retrieval in textual corpora - Sallaberry, Christian (London, ISTE Ltd. ; Hoboken, N.J. : Wiley, 2013)
This book addresses the field of geographic information extraction and retrieval from textual documents. Geographic information retrieval is a rapidly emerging subject, a trend fostered by the growing power of the Internet and the emerging possibilities of data dissemination. After positioning his work in this field in Chapter 1, the author makes proposals in the following two chapters. Chapter 2 focuses on spatial and temporal information indexing and retrieval in corpora of textual documents. Propositions for both spatial and temporal information retrieval (IR) are made.
3.5.3. Evaluation of the multicriteria IR applied to tiling; 3.6. Summary; 3.6.1. Contributions; 3.6.2. Perspectives; Chapter 4. General Conclusion; 4.1. Summary; 4.1.1. Contributions to the access by geographic content to textual corpora; 4.1.2. Spatial and temporal IR in texts; 4.1.3. Multicriteria IR in texts; 4.2. Perspectives; 4.2.1. Intradimensional axis; 4.2.2. Interdimensional axis; 4.2.3. Expansion of the vocabulary for a qualitative representation of the geographic dimensions; Bibliography; Index.
Includes bibliographical references (pages 105-121) and index.
Online resource; title from PDF title page (Wiley, viewed August 26, 2013).
Keywords: Geographic information systems; Geography -- Data processing; Information storage and retrieval systems -- Geography; Management -- Geographic information systems; SCIENCE -- Earth Sciences -- Geography; TRAVEL -- Budget; TRAVEL -- Hikes & Walks; TRAVEL -- Museums, Tours, Points of Interest; TRAVEL -- Parks & Campgrounds; Geographic information systems; Electronic books